Evaluation of Hot‐Melt Extrusion and Injection Molding for Continuous Manufacturing of Immediate‐Release Tablets. Issue 6 (11th March 2015) - Melocchi, Alice; Loreti, Giulia; Del Curto, Maria Dorly; Maroni, Alessandra; Gazzaniga, Andrea; Zema, Lucia
<x xml:space="preserve">Abstract</x> The exploitation of hot‐melt extrusion and injection molding for the manufacturing of immediate‐release (IR) tablets was preliminarily investigated in view of their special suitability for continuous manufacturing, which represents a current goal of pharmaceutical production because of its possible advantages in terms of improved sustainability. Tablet‐forming agents were initially screened based on processability by single‐screw extruder and micromolding machine as well as disintegration/dissolution behavior of extruded/molded prototypes. Various polymers, such as low‐viscosity hydroxypropylcellulose, polyvinyl alcohol, polyvinyl alcohol–polyethylene glycol graft copolymer, various sodium starch glycolate grades (e.g., Explotab® CLV) that could be processed with no need for technological aids, except for a plasticizer, were identified. Furthermore, the feasibility of both extruded and molded IR tablets from low‐viscosity hydroxypropylcellulose or Explotab® CLV was assessed. Explotab® CLV, in particular, showed thermoplastic properties and a very good aptitude as a tablet‐forming agent, starting from which disintegrating tablets were successfully obtained by either techniques. Prototypes containing a poorly soluble model drug (furosemide), based on both a simple formulation (Explotab® CLV and water/glycerol as plasticizers) and formulations including dissolution/disintegration adjuvants (soluble and effervescent excipients) were shown to fulfill the USP 37 dissolution requirements for furosemide tablets. © 2015 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 104:1971–1980, 2015